2019
DOI: 10.17219/dmp/110432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of piezocision-assisted flapless corticotomy in the retraction of four upper incisors: A randomized controlled clinical trial

Abstract: Background. Comprehensive orthodontic treatment may last for 20-24 months. Reducing the treatment time has become a common demand from both patients and orthodontists. Minimally invasive piezocision is one of the suggested approaches to accelerate the orthodontic tooth movement. Objectives. The aim of this randomized controlled clinical trial was to assess the effectiveness of the flapless piezocision procedure in accelerating the retraction of upper incisors. Material and methods. A single-blinded, parallel-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 24 publications
0
47
1
3
Order By: Relevance
“…This is statistically significant, but we cannot say if it would be clinically significant, as the mean treatment duration varies between 19-34 months. [2] For maxillary incisors' retraction, Al-Imam et al [40] found a statistically significant increase in the rate of retraction. According to this study [40] palatal and labial piezocision decreased the time of incisors' retraction by 3 weeks when compared to incisors' retraction without piezocision.…”
Section: Plos Onementioning
confidence: 98%
See 4 more Smart Citations
“…This is statistically significant, but we cannot say if it would be clinically significant, as the mean treatment duration varies between 19-34 months. [2] For maxillary incisors' retraction, Al-Imam et al [40] found a statistically significant increase in the rate of retraction. According to this study [40] palatal and labial piezocision decreased the time of incisors' retraction by 3 weeks when compared to incisors' retraction without piezocision.…”
Section: Plos Onementioning
confidence: 98%
“…The summary findings are presented in Fig 2, Table 2, and S3 Table. Most of the RCTs were classified as having a high risk of bias. Only one study [32] was judged as having a low risk of bias, and three studies [33][34][35] were judged in the "some concerns" category. The two CCTs were having a serious risk of bias because of a lack of information regarding missing data.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 3 more Smart Citations